Request Strategies: A Comparative Study in Mandarin Chinese and Korean - Rue, Yong ju; Zhang, Grace (John Benjamins, 2008)
This book investigates request strategies in Mandarin Chinese and Korean, and is one of the first attempts to address cross-cultural strategies employed in the speech act of requests in two non-Western languages. The data, drawn from role-plays and naturally recorded conversations, complement each other in terms of exhaustiveness and authenticity.This study explores the similarities and differences of the request patterns that emerged in the Chinese and Korean data, and the intricate relation between request strategies and social factors (such as power and distance). The findings raise questions about the influence of methodology on data, and the applicability of so called universals to East Asian languages. They also offer new insights into generally-held ideas of directness and requesting behaviours in Chinese and Korean, and the problems of cross-cultural and cross-linguistic communication.This research is suggestive for the disciplines of cross-cultural pragmatics, cross-cultural communication, contractive linguistics, applied linguistics and discourse analysis.Table of contentsPrefaceAbbreviations, conventions and notations1. Introduction2. Previous studies3. Methodology4. Individual situation comparisons5. Comparisons of social variables6. General discussion7. Sequential analysis of turn-taking8. ConclusionsAppendix: Request scenariosReferencesGlossary of technical termsName indexSunject index